MCP3 POLYMORPHISM, ENVIRONMENTAL RISK FACTORS AND ASTHMA- A HOSPITAL BASED STUDY IN VELLORE - MANJIMA CHATTERJEE,; UPASANA MUKHERJEE,; NARMADA ASHOK,; RAJA DAS,; SUVRAJIT DAS,; RADHA SARASWATHY, (International Journal of Pharma and Bio Sciences, 2016)
Asthma being a chronic disease imposes a substantial burden on the community with greater morbidity and frequent exacerbations. Environment and genetic factors strongly contribute towards asthma. This study aims to understand the demographic characteristics of asthma patients and to investigate the presence of genetic polymorphism in the MCP3 gene in Vellore, India. A total of 119 confirmed asthma patients (clinically and pulmonary function tests) were analysed for the demographic profile with the presence of genetic polymorphism in MCP3 promoter (-1381T/C) and intronic regions (+563C/T) using PCR-SSCP (Single Strand Conformation Polymorphism) and Sanger sequencing. Two to three of the risk factors and symptoms were significantly associated with asthma. Only one patient with a novel variation (+563C/T) in MCP3 second intronic region was observed. The study being the first of its kind infers a modification of triggering factors and environmental constraints could lead to a better control of the disease.